Loss-of-Function Mutations in YY1AP1 Lead to Grange Syndrome and a Fibromuscular Dysplasia-Like Vascular Disease. - Guo, Dong-Chuan; Duan, Xue-Yan; Regalado, Ellen S; Mellor-Crummey, Lauren; Kwartler, Callie S; Kim, Dong; Lieberman, Kenneth; de Vries, Bert B A; Pfundt, Rolph; Schinzel, Albert; Kotzot, Dieter; Shen, Xuetong; et al. (Am J Hum Genet, 2017)
Fibromuscular dysplasia (FMD) is a heterogeneous group of non-atherosclerotic and non-inflammatory arterial diseases that primarily involves the renal and cerebrovascular arteries. Grange syndrome is an autosomal-recessive condition characterized by severe and early-onset vascular disease similar to FMD and variable penetrance of brachydactyly, syndactyly, bone fragility, and learning disabilities. Exome-sequencing analysis of DNA from three affected siblings with Grange syndrome identified compound heterozygous nonsense variants in YY1AP1, and homozygous nonsense or frameshift YY1AP1 variants were subsequently identified in additional unrelated probands with Grange syndrome. YY1AP1 encodes yin yang 1 (YY1)-associated protein 1 and is an activator of the YY1 transcription factor. We determined that YY1AP1 localizes to the nucleus and is a component of the INO80 chromatin remodeling complex, which is responsible for transcriptional regulation, DNA repair, and replication. Molecular studies revealed that loss of YY1AP1 in vascular smooth muscle cells leads to cell cycle arrest with decreased proliferation and increased levels of the cell cycle regulator p21/WAF/CDKN1A and disrupts TGF-β-driven differentiation of smooth muscle cells. Identification of YY1AP1 mutations as a cause of FMD indicates that this condition can result from underlying genetic variants that significantly alter the phenotype of vascular smooth muscle cells.
Keywords: Adolescent; Adult; Bone and Bones; Brachydactyly; Cell Cycle Checkpoints; Exome; Female; Fibromuscular Dysplasia; Genes, Recessive; Heterozygote; Homozygote; Humans; Learning Disorders; Male; Middle Aged; Muscle, Smooth, Vascular; Mutation; Nuclear Proteins; Pedigree; Syndactyly; Syndrome; Transcription Factors